PENGEMBANGAN DESAIN PEMBELAJARAN BERBASIS REALISTIC MATHEMATICS EDUCATION UNTUK TOPIK PELUANG DI KELAS XII SMA - Gusti Rada (Departemen Matematika, 2019)
The result of preliminary studies suggest that students’ mathematical reasoning abilities on topic probability was low. This is due to the teaching of teachersthat are too focused on textbooks, while the presentation of topic probability is not fully adequate to guide students in learning.This research aimed to developing instructional design with the Realistic Mathematic Education (RME) approach on topic probability for Senior High School grade XII using Gravemeijer and Cobb model which consists of three phases, namely the preparing for the experiment), the conducting experiment) and the retrospective analysis.The subjects research were SMAN 2 Painan grade XII. The learning design in question is a learning path known as the Hypotetical Learning Trajectory (HLT). HLT is a learning flow consisting of learning objectives, learning activities, and learning process hypotheses to predict how students' thoughts and understanding will develop in the context of learning activities.The result showed that the development of instructional learning design with realistic mathematic education on topic probability in senior high school grade XII was valid and practice.Keywords–Realistic Mathematics Education, Probability, Design Research, Hypotetical Learning Trajectory